Analisis Validitas, Praktikalitas, dan Efektifitas Pengembangan Bahan Ajar Terintegrasi Konten Kecerdasan Spiritual pada Materi Fisika Tentang Vektor dan Gerak Lurus - Sepna Gitnita; Zulhendri Kamus; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2018)
The 2013 Curriculum requires learning to achieve overall competence of spiritual competence, social, knowledge, and skills competencies. In fact, the demands of the 2013 curriculum are not fully implemented. One factor is the lack of learning resources to support the achievement of the competencies of students demanded by the 2013 Curriculum, especially spiritual attitudes. The altervative solution to this problem is developing physics teaching materials that integrating the content of the value of spiritual intelligence. This research includes the type of research and development (R & D). This method consists of ten steps, but this research uses only six steps: potential and problems, data collection, product design, design validation, design revisions, and product testing. The object of research is the subject of physics with the content of spiritual intelligence. The instrument used in this research is the validity assessment sheet, the practicality assessment sheet, and the test result sheet. Based on data analysis, four results of this research are presented. First, teaching materials with the content of spiritual intelligence values of vector material and straight motion are in accordance with the structure of teaching materials and there are values of spiritual intelligence relevant to the concept of physics. Second, the value of the validity of teaching materials with the content of spiritual intelligence values of vector material and straight motion is very high with an average value of 86.55. Third, teaching materials with spiritual values of spiritual intelligence are practically used by teachers and students, with practical values of 83.87 and 80.54, respectively. Fourth, teaching materials with the content of spiritual intelligence values are effectively used in a scientific approach to improving the competence of learners' knowledge.